Photocell Sensor Implementation as an Automatic Lighting System for Public Street Lighting - Ojak Abdul Rozak; Nurkahfi Irwansyah; Hedy Aditya Baskhara; Heri Kusnadi (Institut Teknologi Nasional, Bandung, 2023)
Nowadays, the demand for electrical energy has experienced exponential growth due to the need for energy sustainability and economic growth in society. However, this increase of electrical energy consumption leads to the high cost of electricity bills. To address the issue, this PKM (Community Service Program) aimed at reducing electricity costs through the re-structurization of the PJU (Public Street Lighting) systems. The method used in this activity included planning and implementing the installation of PJU lighting and automatic systems involving local youth to provide them with hands-on knowledge and practical experiences in installing automatic systems directly on 11 units of PJU lights utilizing eight (8) photocells as the main components. The result of this community service activity showed the feasibility and effectiveness of the electrical installation and automatic system for PJU lights using 8 pcs of LDR on 11 electric poles along the roads in the area.